Trace element compositions of the clinopyroxene from andesites from the Kueishantao island analysed by LA-ICP-MS (S6) - Kun Guo; Xiaoyuan Wang; Shuai Chen (PANGAEA, 2021)
This dataset reports in situ trace elements of clinopyroxene of andesite from Kueishantao, north of Taiwan, China. Trace element compositions were obtained with LA-ICP-MS at the Wuhan Sample Solution Analytical Technology Co., Ltd.
In: Guo, K et al. (2021): In situ elemental, Sr isotope composition of plagioclase and elemental composition of clinopyroxene and thermobarometric data of andesite from Kueishantao, north of Taiwan, China [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.929297